(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Solid fats come mainly from animal fats or vegetable oils in the form of hydrogenated oil with a melting point of 36-43 by hydrogenation with hydrogen in the presence of catalysts. The following raw materials were used for the study: Nisosel-820 catalyst containing 25% nickel metal from the Netherlands, a single-use catalyst with a reduced activity of 30%; beef fat with melting point 26 ℃; cottonseed oil with a iodine content of 112% and dry hydrogen gas were obtained. The hydrogenated oil was obtained on the basis of the following technology: cottonseed oil and beef fat were first selected in a ratio of 50:50. In this experiment, we can see that 20 ℃ 29% and 38% of the 1st and 2nd samples have curves, and in general the minimum crystallization requirement is that the amount of solid triglyceride at 20 ℃ should not be less than 23%. This means that the obtained hydrotransesterification parameters satisfy the law